A high performance redox-mediated electrolyte for improving properties of metal oxides based pseudocapacitive materials. (20th December 2015) - Han, Wei; Kong, Ling-Bin; Liu, Mao-Cheng; Wang, Dan; Li, Jia-Jia; Kang, Long
Highlights: A novel redox-mediated aqueous electrolyte is prepared by adding sodium persulfate (Na2 S2 O8 ) into KOH alkaline electrolyte for the application in most metal oxide based supercapacitors. When added the Na2 S2 O8 mediated in KOH electrolyte, the charge time is shorted and the discharge time is increased sharply. This new redox-mediated aqueous electrolyte not only suitable for the metal oxide based electrode, but also have much effect to the metal sulfide, vanadate, and phosphate electrode et al. Abstract: A novel redox-mediated aqueous electrolyte is prepared by adding sodium persulfate (Na2 S2 O8 ) into KOH alkaline electrolyte for the application in most metal oxide based supercapacitors. The electrochemical behaviors of nickel oxide (NiO) electrode in 2 M KOH and 2 M KOH containing different concentration of Na2 S2 O8 electrolytes, respectively, were characterized by cyclic voltammetry and electrochemical impedance spectroscopy methods. The results indicate that the reaction mechanism of NiO electrode in Na2 S2 O8 mixed electrolytes appears to be the reversible redox of Ni 2+ to Ni 3+ on two different channels, which is different with that in KOH electrolyte. Charge-discharge experiments show that the discharge ability of the NiO electrode in redox electrolyte is excellent. When added Na2 S2 O8 into KOH electrolyte, the charge time is shorted and the discharge time is increased sharply. The specific capacitance was up to 6317.5 F g −1 at 0.5 A g −1 in mixed 2 M KOH and 0.03 M Na2 S2 O8, more than 100% coulombic efficiency. Fortunately, this new redox-mediated aqueous electrolyte not only suitable for the metal oxide based electrode, but also have much effect to the metal sulfide, vanadate, and phosphate electrode et al.